Fintech Peer-to-Peer Lending (P2PL): A Long-Term Microeconomic Finance Problem in Indonesia - Riendita Restu Pardani; Febrian Kwarto (Transpublika Publisher, 2025)
This study analyzes the long-term impact of Fintech Peer-to-Peer (P2P) Lending on Indonesia's microeconomy. These platforms have rapidly expanded, improving financial access for those underserved by traditional institutions. While P2P lending offers easy loan access and promotes financial inclusion, concerns exist regarding its effect on borrowers' long-term financial stability and the microeconomy as a whole. Using a descriptive qualitative method and case studies, the research gathered insights from borrowers, P2P providers, and consumer protection experts through in-depth interviews. Results indicate that, despite providing short-term solutions, P2P lending presents risks such as rising debt, high default rates, and inadequate credit oversight. Additionally, regulatory uncertainties and low public financial literacy further compound these challenges. The study calls for stricter regulations, enhanced financial education, and greater transparency from P2P lending providers. The findings aim to help policymakers develop effective strategies to maximize the benefits of financial innovation while minimizing long-term risks for all stakeholders.